A patient with isolated adrenocorticotropin deficiency presenting with repetitive oesophageal ulcer and stenosis. (29th December 2010) - Tamiya, Hiroyuki; Ishikawa, Akihisa; Mano, Shinya; Kamoshida, Toshiro; Hirai, Shinji; Chikatsu, Noriko; Oka, Yuji
Abstract : Isolated adrenocorticotropic hormone (ACTH) deficiency (IAD) is a potentially fatal condition that is difficult to diagnose. The authors diagnosed IAD in a patient who presented with recurrent oesophageal ulceration resulting in oesophageal stenosis. The recurrent oesophageal ulcers were due to frequent nausea and vomiting that were the presenting digestive symptoms of adrenal insufficiency. Severe hypoglycaemia during this patient's course suggested the diagnosis of adrenal insufficiency. This case is educational because digestive symptoms are the most common symptoms in patients with adrenal insufficiency, but the diagnosis of adrenal insufficiency in such patients is not easy.